2000
DOI: 10.1111/j.1651-2227.2000.tb01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of infections for three‐month length increment in young children in rural Zambia

Abstract: It was the aim of this study to describe the relationship of infections with subsequent 3-mo length increment in children below 2 y of age in rural Zambia. Children aged 6-9 mo ('infants'; n = 84) and 14-20 mo ('toddlers'; n = 81) attending Mother-and-Child Health clinics, were included and followed up after 3.0 mo (min-max; 2.1-3.7 mo). Anthropometric measurements were taken at each visit. At baseline, C-reactive protein (CRP), alpha1-acid glycoprotein (AGP), retinol and malaria parasitaemia were assessed. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
2
3
0
1
Order By: Relevance
“…Similar results were found in a study on infection, length growth and acute phase proteins, such as AGP. It was reported that AGP is negatively correlated with retardation in growth [Hautvast et al, 2000]. Our findings of a negative correlation coefficient in only one parameter can be explained by assuming two counteracting mechanisms.…”
Section: Discussionsupporting
confidence: 47%
“…Similar results were found in a study on infection, length growth and acute phase proteins, such as AGP. It was reported that AGP is negatively correlated with retardation in growth [Hautvast et al, 2000]. Our findings of a negative correlation coefficient in only one parameter can be explained by assuming two counteracting mechanisms.…”
Section: Discussionsupporting
confidence: 47%
“…In public health assessments, micronutrient status is commonly determined by using concentrations in blood as a surrogate for total body status. Blood concentrations of retinol, iron, and zinc can be altered by the APR to infection ( Table 2) (21)(22)(23)124,(127)(128)(129)(130)(131)(132)(133)(134)137,(145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160). Alterations in blood micronutrient concentrations result from hepatic suppression of transport proteins (RBP, transthyretin, albumin, and transferrin) and increases in serum ferritin and hepatic metallothionein, positive APPs that assist in iron and zinc sequestration, respectively (28,98,(161)(162)(163)(164).…”
Section: Apps As Markers Of Infection For Nutrition Interventionsmentioning
confidence: 99%
“…These effects are probably part of an adaptive response to withhold key nutrients from invading pathogens, but they can result in inadequate availability of certain nutrients to support growth, even if intake is adequate, during the period of metabolic disturbance. Among children 6–20 months of age in Zambia, blood markers of inflammation (usually associated with infection) were negatively related to growth in length during the subsequent 3 months (Hautvast et al . 2000).…”
Section: What Is the Role Of Subclinical Infections And Related Condimentioning
confidence: 99%